The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5433/1679-0359.2017v38n3p1161
|View full text |Cite
|
Sign up to set email alerts
|

Germination and vigor of linseed seeds under different conditions of light, temperature and water stress

Abstract: Linseed (Linum usitatissimum L.), cultivated from seeds, is one of the oldest plants domesticated by humans and is popularly used as a medicine. It can be used as the raw material to produce oil and bran because it has high lipids content, fiber and proteins. Based on the economic potential of this species and the need for more information about its physiology, the goal of this study was to analyze the effects of light, temperature and water stress on the germination and vigor of linseed seeds. In experiment I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Rossetto (1997) also verified that as the water potential reduced, there was a loss of soybean seeds performance in the first germination test count. In flax seeds, Stefanello et al (2017) observed that osmotic potentials equal to or lower than -0.30 MPa were harmful to germination, and that there was no normal seedling development up from -0.50 MPa concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Rossetto (1997) also verified that as the water potential reduced, there was a loss of soybean seeds performance in the first germination test count. In flax seeds, Stefanello et al (2017) observed that osmotic potentials equal to or lower than -0.30 MPa were harmful to germination, and that there was no normal seedling development up from -0.50 MPa concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The seeds were distributed on three sheets of paper moistened with distilled water at the proportion of 2.5 times the weight of the paper. After sowing, the plastic boxes were maintained in BOD (Biochemical Oxygen Demand) chambers at 15, 20, 25 and 30°C, in the presence and absence of light (Luz et al, 2014;Stefanello, Viana, & Neves, 2017). Counting was made every three days for 21 days.…”
Section: Methodsmentioning
confidence: 99%
“…For the absence of light, the seeds were sown in a room where the light was filtered with three green cellophane paper sheets. The germination boxes were maintained in the dark throughout the test by covering them with two sheets of aluminum foil (Stefanello et al, 2017). The evaluations for the condition without light were made in the room with filtered light.…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Varga et al (2020), it was determined that L. usitatissimum seeds did not differ in germination with medium temperatures of 10 C (58%) and 20 C (59%) on the 7th day of the experiment under different salt stress conditions. Kurt and Bozkurt (2006) reported that the emergence and germination rate of L. usitatissimum seeds enhanced as the temperature increased from 10 to 30 C, and they obtained the best emergence rate (86.9%) at 30 C. Stefanello et al (2017) examined 15, 20, 25, and 30 C as germination temperature for L. usitatissimum seeds and found the best results at 20 C (79%), where 15 and 25 C (68%) showed slightly lower germination. It can be concluded that the optimum temperature required for the seed germination varies according to the species and the ecology in which the seeds of the species are collected (Fenner & Thompson, 2005;Yilmaz & Tonguç, 2013).…”
Section: Effect Of Different Treatments On Seed Germination Rate Of L...mentioning
confidence: 99%
“…There are several taxonomic studies on natural Linum species found in Turkey, as well as agronomic and phylogenetic studies on commercially used Linum species (Yılmaz et al, 2011). Studies on the germination of Linum seeds focused on L. usitassisimum , which is widely used in agriculture (Bakhit & Moradi, 2017; Stefanello et al, 2017). There are no studies on the production and ornamental plant potential of other Linum species, especially endemic ones.…”
Section: Introductionmentioning
confidence: 99%